Modification of Outer Membrane Protein Profile and Evidence Suggesting an Active Drug Pump in Enterobacter aerogenes Clinical Strains - Gayet, Stéphane (American Society for Microbiology, 2003)
Two clinical strains of Enterobacter aerogenes that exhibited phenotypes of multiresistance to β-lactam antibiotics, fluoroquinolones, chloramphenicol, tetracycline, and kanamycin were investigated. Both strains showed a porin pattern different from that of a susceptible strain, with a drastic reduction in the amount of the major porin but with an apparently conserved normal structure (size and immunogenicity), together with overproduction of two known outer membrane proteins, OmpX and LamB. In addition, the full-length O-polysaccharide phenotype was replaced by a semirough Ra phenotype. Moreover, in one isolate the intracellular accumulation of chloramphenicol was increased in the presence of the energy uncoupler carbonyl cyanide m-chlorophenylhydrazone, suggesting an energy-dependent efflux of chloramphenicol in this strain. The resistance strategies used by these isolates appear to be similar to that induced by stress in Escherichia coli cells.